Single strand mRNA differential display (SSDD) applied to the identification of serine/threonine phosphatases regulated during cerebellar development - Vilá Ortiz, Guillermo J. (2001)
Differential display is a used widely and useful technique for the study of differentially expressed genes. However, very poor results have been obtained in the past when particular gene families were studied. Initially, we attempted to study the mRNA expression of catalytic subunits of serine/threonine phosphatases, using two primers specific to consensus sequences of these phosphatases. When differential display was applied, two wide, unresolved bands were isolated that contained cDNA of several phosphatases, together with that of many other unrelated transcripts. To overcome this problem, we used an alternative strategy, referred to as single strand differential display (SSDD), which is a combination of differential display and single strand conformation polymorphism (SSCP). After initial PCR amplification with specific primers, we ran a polyacrylamide (or agarose) gel, pre-selecting the region that contained fragments of the size expected for the consensus region (250-350 bp). The DNA eluted from this zone was then separated on a non-denaturing (SSCP) gel. Using this approach, we were able to characterize the expression of five ser/thr phosphatases, and a previously unreported splice variant of one of them, PP1γ. All these phosphatases show varying levels of expression during development, indicating a very complex regulation of protein phosphorylation-dephosphorylation during the period of synaptogenesis in the mouse cerebellum.